Spillovers Among Interest Rates, Bond Yields, Stock Market Returns, and Exchange Rates: Evidence from South Asian Economies - Saleem, Hassan Mujtaba Nawaz; Mazhar, Fatima; Ahmad, Rashid; Yousuf, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
This paper analyses how Bond yields, Inflation, and GDP Growth may influence Interest rates, Stock Market Returns, and Exchange rates in South Asian countries i.e. India, Pakistan, Bangladesh, Sri Lanka, and Nepal. Panel data has been collected from the World Bank and IMF for the years 2000-2023. From judging the results, the Pooled Mean Group has been used. The analysis reveals that interest rates in South Asian economies are significantly influenced by bond yields, inflation, and GDP growth. Stock market returns are driven by bond yields and trade openness, while inflation plays a key role in determining exchange rate movements. These relationships are economically justified based on classical economic theories of monetary policy, portfolio diversification, and trade openness. The significant coefficients suggest that policymakers in South Asia should consider these factors when formulating monetary and financial policies to achieve financial stability and inclusive growth. Policymakers should enhance coordination between monetary and fiscal policies, monitor bond market activities, and adjust policy rates based on inflation targets. Strengthening inflation-targeting frameworks and adopting a counter-cyclical monetary policy can help manage inflation expectations and prevent overheating during economic booms and slowdowns.